2017
DOI: 10.1111/jocn.13416
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life improves in patients with chronic heart failure and Cheyne‐Stokes respiration treated with adaptive servo‐ventilation in a nurse‐led heart failure clinic

Abstract: Chronic heart failure patients come regularly to the nurse-led heart failure clinic. The heart failure nurses' competency has to include knowledge of equipment to provide support and continuity of care to the patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Prior research has demonstrated that nurse-led heart failure clinics can contribute to the reduction of unplanned heart failure hospitalizations. 10,15,17,34,35 Coupling this strategy with nurse-performed ultrasound of the pleural space and lungs to monitor pulmonary congestion has the potential to further improve outcomes and possibly decrease costs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior research has demonstrated that nurse-led heart failure clinics can contribute to the reduction of unplanned heart failure hospitalizations. 10,15,17,34,35 Coupling this strategy with nurse-performed ultrasound of the pleural space and lungs to monitor pulmonary congestion has the potential to further improve outcomes and possibly decrease costs.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 Both in the US and Europe, nurses are managing heart failure patients in conjunction with physicians. [9][10][11][12] Furthermore, in resource-limited settings, nurses and community health workers may represent the primary providers for both acute and chronic heart failure patients. LUS performed by these providers may allow for lower-cost and more effective management of these patients.…”
Section: Introductionmentioning
confidence: 99%
“…Patients were followed up via telephone call by nurse-specialists at 12 weeks (±5 days) after discharge. Study endpoints include the following domains: 1) the rate of medications adherence; in specific, during the follow-up, patients were asked by investigators how often they missed taking their medications, and medication adherence was defined as taking medications during >80% of the follow-up period, and medications refilled in the electronic healthcare system were used to confirm medications adherence; 2) the differences in QoL as assessed by the Short Form-12 (SF-12) physical and mental component scores (PCS and MCS) [17]; and 3) the incident rate of rehospitalization due to CHF exacerbation and all-cause mortality.…”
Section: Study Follow-up and Endpointsmentioning
confidence: 99%
“…In total, 51 HF patients were enrolled and thereafter received adaptive servo-ventilation for trial evaluation. Results show that this treatment may improve the QOL of HF patients ( 13 ).…”
Section: Roles Of Nursing In the Management Of Geriatric Cvdmentioning
confidence: 98%